Data Management Technologies and Applications : Third International Conference, DATA 2014, Vienna, Austria, August 29-31, 2014, Revised Selected papers - Helfert, Markus; Holzinger, Andreas; Belo, Orlando; Francalanci, Chiara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the Third International Conference on Data Technologies and Applications, DATA 2014, held in Vienna, Austria, in August 2014. The 12 revised full papers were carefully reviewed and selected from 87 submissions. The papers deal with the following topics: databases, data warehousing, data mining, data management, data security, knowledge and information systems and technologies; advanced application of data.
Databases -- Data warehousing -- Data mining -- Data management -- Data security -- Knowledge and information systems and technologies -- Advanced application of data.
Keywords: Database management; Information storage and retrieva; Data mining; Database Management; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).